How do you simplify # -3[(x-2) + 5(x-2)]#?

1 Answer
Jan 31, 2017

Answer:

See the entire simplification process below:

Explanation:

First, expand the terms within parenthesis within the brackets. Be sure to manage the signs of the individual terms correctly:

#-3[(x - 2) + 5(x - 2)] -> -3[x - 2 + 5x - 10]#

Next group and combine like terms within the brackets:

#-3[x - 2 + 5x - 10] -> -3[x + 5x - 2 - 10] -> -3[6x - 1]#

Now, multiple each term within the brackets by #-3#:

#-3[6x - 1] -> (-3 xx 6x) + (-3 xx -1) ->#

#-18x + 3# or #3 - 18x#